THE EFFECT OF SOCIAL MEDIA IN IMPROVING STUDENTS’ WRITING SKILL - Suswati, Rita; Saleh, Syarbaini; Putri, Citra Anggia; Nuran, Ade Aini (UPI Press, 2019)
The effect of social media in improving students’ writing skill is investigated in this paper, which can be used to improve students’ creativity in writing. This paper takes covering of second semester English education students of Universitas Negeri Medan that study written language skills. The method used in this research is the development research aims to produce written language skills learning materials using social media (instagram, facebook whatsapp). Its intention to answer the students’ need of the innovated material and to find out the level of students creativity after using such materials. Further, this paper gives a simpler and practical method to develop learning material using social media to improve students’ creativity in writing.